PROJECT-BASED BUSINESS MANAGEMENT TRAINING FOR WOMEN'S ENTREPRENEURIAL SKILLS DEVELOPMENT - Nurhayati, Sri; Handayani, Farida Arianti (Jurnal Visi Ilmu Pendidikan, 2025)
This study explores the implementation and effectiveness of Project-Based Learning (PjBL) in a business management training program for women entrepreneurs at An Nur Ibun Community Learning Center. Using a qualitative case study approach, data were collected through interviews with participants and facilitators, focusing on the experiences, challenges, and outcomes of the PjBL approach. The findings reveal that PjBL significantly enhanced participants' entrepreneurial competencies, particularly in financial management, marketing strategies, and strategic planning. The hands-on, practical nature of PjBL allowed participants to apply theoretical knowledge directly to their businesses, resulting in increased confidence and improved business practices. The collaborative environment fostered by PjBL promoted teamwork and problem-solving skills, while continuous support from facilitators helped participants overcome challenges related to varying prior knowledge and digital tool usage. Despite some initial difficulties, the integration of digital tools and the structured six-step PjBL approach contributed to tangible improvements in participants' business operations. The study highlights the importance of tailored support, flexible teaching strategies, and the integration of practical tasks in business training programs. The research underscores PjBL's effectiveness as a pedagogical approach for developing essential entrepreneurial skills and recommends further exploration of strategies to maximize its benefits in diverse learning contexts.